Re-examine The Long Term Post-merger Performance of Acquirers: UK Evidence - Luo, Ting (2006)
In the past decades, many papers have focused on the stock performance after an M&A deal. The results have shown that, for the target companies there is a generally acceptable conclusion that they receive economically large and statistically significant wealth gain in both US and UK studies. However, for those bidder firms, the reported return is still ambiguous, especially the long term post-merger performance of acquirers. There is also evidence that the stock abnormal return depends on the method of payment, the premium, the financial status of the acquired company etc.